Photophysics of Fluorescent Contact Sensors Based on the Dicyanodihydrofuran Motif. Issue 2 (4th December 2020) - Suhina, Tomislav; Bonn, Daniel; Weber, Bart; Brouwer, Albert M.
Abstract: Fluorescent molecular rotors have been used for measurements of local mobility on molecular length scales, for example to determine viscosity, and for the visualization of contact between two surfaces. In the present work, we deepen our insight into the excited‐state deactivation kinetics and mechanics of dicyanodihydrofuran‐based molecular rotors. We extend the scope of the use of this class of rotors for contact sensing with a red‐shifted member of the family. This allows for contact detection with a range of excitation wavelengths up to ∼600 nm. Steady‐state fluorescence shows that the fluorescence quantum yield of these rotors depends not only on the rigidity of their environment, but – under certain conditions – also on its polarity. While excited state decay via rotation about the exocyclic double bond is rapid in nonpolar solvents and twisting of a single bond allows for fast decay in polar solvents, the barriers for both processes are significant in solvents of intermediate polarity. This effect may also occur in other molecular rotors, and it should be considered when applying such molecules as local mobility probes. Abstract : Either way : Molecular fluorescent rotors based on the DCDHF motif can decay via twisting of two different bonds, with different sensitivities to solvent polarity. An implication of this mechanistic complexity is that their fluorescence intensity may depend on viscosity and polarity. Nonetheless, two probes that differ only in their conjugation length can both be used fruitfully to monitor viscosity and mechanical contact. The high local pressure in the mechanical contact leads to confinement